20.0% Efficiency Si Nano/Microstructures Based Solar Cells with Excellent Broadband Spectral Response. (8th February 2016) - Huang, Zengguang; Song, Xiaomin; Zhong, Sihua; Xu, Haiyuan; Luo, Wenxing; Zhu, Xudong; Shen, Wenzhong
Abstract : Spectral response of solar cells determines the output performance of the devices. In this work, a 20.0% efficient silicon (Si) nano/microstructures (N/M‐Strus) based solar cell with a standard solar wafer size of 156 × 156 mm 2 (pseudo‐square) has been successfully fabricated, by employing the simultaneous stack SiO2 /SiN x passivation for the front N/M‐Strus based n + ‐emitter and the rear surface. The key to success lies in the excellent broadband spectral responses combining the improved short‐wavelength response of the stack SiO2 /SiN x passivated Si N/M‐Strus based n + ‐emitter with the extraordinary long‐wavelength response of the stack SiO2 /SiN x passivated rear reflector. Benefiting from the broadband spectral response, the highest open‐circuit voltage ( V oc ) and short‐circuit current density ( J sc ) reach up to 0.653 V and 39.0 mA cm −2, respectively. This high‐performance screen‐printed Si N/M‐Strus based solar cell has shown a very promising way to the commercial mass production of the Si based high‐efficient solar cells. Abstract : A 20.0%‐efficiency, large‐size silicon nano/microstructure (N/M‐Strus)‐based solar cell with excellent broadband spectral response is successfully fabricated by employing the simultaneous stack SiO2 /SiN x passivation for the front N/M‐Strus based n + ‐emitter and the rear surface. This high‐performance screen‐printed Si N/M‐Strus based solar cell is a very promising way towards the commercial mass production of Si‐based high‐efficiency solar cells.